L'habit ne fait pas le moine: Antonine Maillet, Translation, and Acadian Identity - LeBlanc, Danielle (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
As a language essentially transplanted from sixteenth-century France, carrying with it the rich heritage and history of the Acadian people, the parlure acadienne [Acadian way of expression] proves central in asserting cultural identity in translation. Using two case studies from Canada’s two primary literary translation practices, French-to-English and English-to-French, this dissertation will argue that Acadian identity, in language and ideology, is expressed through hybridity in translations whose target audiences are non-Acadian. First, two English translations of Antonine Maillet’s works, The Tale of Don l’Orignal (1978/2004) translated by Barbara Godard and Pélagie: The Return to Acadie (1982/2004) translated by Philip Stratford, will be considered in light of their respective translation strategies to demonstrate that Acadian identity is expressed through respect of the parlure acadienne’s linguistic and figurative aspects. Its expression can be interpreted in terms of what Michael Cronin calls a micro-cosmopolitan view of translation that pays attention to singularity and where difference and diversity manifest themselves within the particular. This discussion will set the stage for arguing that Antonine Maillet incorporates the parlure acadienne in her translations of Shakespeare’s plays, namely in La Nuit des Rois (1993) and La tempête (1997). Comparing her translations with Shakespeare’s original and with two contemporaneous Québec translations, this dissertation will argue that the Maillet’s linguistic choices are deliberately reminiscent of the parlure acadienne with the purpose of exploring the dynamics of translation on the expression or representation of Acadian identity in an intralingual minority context. Although the Acadian literary tradition is rich and vibrant, little research has been conducted on either the reception of Acadian authors in English Canada or the representation of Acadian identity in Anglo-Canadian translation. Similarly, a few theorists have signalled a sense of Acadian identity in English-to-French literary translation. This dissertation looks to help close those gaps.
Keywords: Literary Translation